XPC exon15 Lys939Gln variant increase susceptibility to prostate adenocarcinoma: Evidence based on 4306 patients and 4779 controls. Issue 28 (10th July 2020) - Qin, Feng; Gao, Sheng-Lin; Xu, Kai; Su, Quan-Xin; Zhang, Ze; Shi, Li; Zhu, Li-Jie; Zhang, Li-Feng; Zuo, Li
Abstract: Background: Previous studies have investigated the correlation between xeroderma pigmentosumcomplementation group C (XPC) variants and prostate adenocarcinoma (PA) risk. Nevertheless, research findings remain inconclusive. Methods: We conducted a pooled analysis to obtain a more accurate estimation of the relationship on XPC exon15 Lys939Gln polymorphism with susceptibility to PA. Moreover, in silico tools were employed to investigate the effect of XPC expression on PA patients' survival time. Results: A total of 4306 patients and 4779 control subjects were assessed. The overall results indicated that XPC Lys939Gln variant was associated with PA risk (recessive genetic model: odds ratio = 1.15, 95% confidence interval = 1.02–1.30, P heterogeneity = .044, P = .021, I 2 = 45.2), especially in Asian descendants. Population-based studies revealed similar results (odds ratio = 1.15, 95% confidence interval = 1.01–1.32, P heterogeneity = .146, P = .040, I 2 = 39.0). In silico tools showed that XPC expression in Caucasian patients was lower than in the normal group. No positive association was observed in African patients. PA subjects with high XPC expression had a longer overall survival time than low expression group. Conclusion: Our findings indicated that XPC Lys939Gln variant might contribute to increased PA susceptibility, especially for Asian patients. Abstract : Supplemental Digital Content is available in the text